O som da integração das tecnologias digitais de informação e comunicação ao currículo: a rádio na internet - voz, poder & aprendizagem - Silva, Jayson Magno da (2011)
The aim of this research is a reflection upon integration of technologies of information to the curriculum. The case study, which was based on the epistemology of Paulo Freire, has as its main plea the use of radio on the internet and takes as starting and arrival point, the voice of the subjects (teacher and student), mediated by the use of technologies in a way of favoring the participation on the curriculum construction and, consequently, the learning process and empowerment. It is a case study about the project called Rádio Jacaré FM (FM Alligator Radio), a pedagogical action that takes shape on the use of radio on the internet, accomplished by a kindergarten teacher and her students from the municipal public network. The research involved the analysis of the directors , the teacher s and sixteen students voices. The research points out, under consideration, that the dialogical action based on Paulo Freire s pedagogy makes the assumption of subjects (teacher and students) while curriculum constructors, by their participation on the radio on the internet, what potentiates the expression of their voices on the classroom dimension which also covers other spaces outside the school and in the digital world